Constraints Perceived by Farmers in Communication Behaviour - Mayank Singh, Rajiv Kumar Singh (Indian Journal of Extension Education, 2022)
Communication is the core activity of human association in general and progress as well as development in particular. No human life can exist in isolation. A man can survive only in society and the survival in society is possible with communication. Therefore, communication is identified as the oldest continued activity of human being since birth and ongoing activity and on till death. More precisely, communication is the basic need of human being and web of society whichmakes the survival, growth, progress and development ofman possible and holds the society intact and progressive. To sum-up, communication is a vital part of personal life in the society. It is equally important in business, education, civilization, administration and other situations where people encounter with each other to satisfy their needs and wishes. The communication system in India is far from showing concern for the problems and needs of the rural folk, the poor people, the workers, peasants’ common people and women. The dite pressure is making it an instrument of consumerism and Counter Reformation. There is not enough political response to these issues as well as the issue of tremendous pressure from the people for a new information order. The extension/communication/dissemination system and network are the key input in increasing the performance in agricultural production. Therefore, the communication is the most powerful input which brings substantial development in socio-economic status of an individual. The studywas conducted inAllahabad district of Uttar Pradesh.